1998
DOI: 10.1557/proc-527-469
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Anion Rotation and Cation Transport in the Plastic High-Temperature Phase of Sodium Ortho-Phosphate

Abstract: The high-temperature phase of sodium ortho-phosphate, α-Na3PO4, belongs to the class of ion conducting plastic crystals, i.e., it is characterized by a dynamic rotational disorder of its poly-atomic anions and, at the same time, by a considerable translational mobility of its cations. During the past decade, the possibility, nature, and importance of a dynamic interplay between the two kinds of motion have been a subject of continued controversy. Proponents of a strong interplay coined the expression “paddle-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This question arises because the X-ray diffraction experiments reveal a particularly short OϪNa distance along the cubic crystal axes involving those sodium ions that are octahedrally surrounded by phosphate groups. Indeed, preliminary Car-Parrinello Molecular-Dynamics calculations do suggest that the mean square displacements of these octahedral cations are somewhat higher than those of the Na ϩ ions in the tetrahedral interstices [54]. On the other hand, the NMR data show no clear evidence for this effect.…”
Section: Discussionmentioning
confidence: 94%
“…This question arises because the X-ray diffraction experiments reveal a particularly short OϪNa distance along the cubic crystal axes involving those sodium ions that are octahedrally surrounded by phosphate groups. Indeed, preliminary Car-Parrinello Molecular-Dynamics calculations do suggest that the mean square displacements of these octahedral cations are somewhat higher than those of the Na ϩ ions in the tetrahedral interstices [54]. On the other hand, the NMR data show no clear evidence for this effect.…”
Section: Discussionmentioning
confidence: 94%
“…Most recently, a strong case in favor of the paddle-wheel mechanism has been presented for the high-temperature phase of sodium orthophosphate, HT-Na 3 PO 4 . From a combination of NMR, inelastic neutron scattering, and electrical conductivity measurements it could be shown that anion rotation and cation transport appear to be highly correlated in this material over a wide range of time and temperature scales. , …”
Section: Introductionmentioning
confidence: 98%
“…From a combination of NMR, inelastic neutron scattering, and electrical conductivity measurements it could be shown that anion rotation and cation transport appear to be highly correlated in this material over a wide range of time and temperature scales. 12,13 The present study is devoted to the low-temperature phase of Na 3 PO 4 which is thermodynamically stable at temperatures below 600 K. The crystal structure of this compound was solved from X-ray and neutron powder diffraction data in the space group P4 h21c. 14 The unit cell contains eight equivalent phosphate tetrahedra whose orientations are perfectly ordered, as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Some salts with complex anions (e.g., Li 2 SO 4 , Na 3 PO 4 ) show phase transitions into a dynamically disordered high-temperature phase (rotor phase) which can be accompanied by a drastic increase in the respective cationic conductivity, caused by the ‘volume effect', , as well as by the ‘paddle-wheel mechanism' . This feature makes the alkali salts of the trifluoromethyl sulfonic acid an interesting class of rotor phases according to the various degrees of rotational freedom of the triflate anion compared to, e.g., the phosphate anion.…”
Section: Introductionmentioning
confidence: 99%